2008
DOI: 10.1113/jphysiol.2008.153346
|View full text |Cite
|
Sign up to set email alerts
|

Cyclothiazide: a subunit‐specific inhibitor of GABAC receptors

Abstract: We tested the effects of cyclothiazide (CTZ), an agent used to block desensitization of AMPA-type glutamate receptors, on heterologously expressed GABA C receptors formed by homomeric ρ subunits. CTZ inhibition of GABA C receptors was subunit specific; it produced a dose-dependent reduction of the GABA-elicited current on homomeric ρ2 receptors with an IC 50 of about 12 μM, but had no significant effect on homomeric ρ1 receptors. This differential sensitivity was attributable to a single amino acid located on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…As shown previously (Singer and Diamond, 2003), blocking AMPAR desensitization with cyclothiazide (CTZ, 50 µM) increased reciprocal GABA release and caused a slower, GABA C R-mediated component to emerge in the reciprocal IPSC (Figure 6A). Although CTZ has been reported to antagonize both GABA A R and GABA C Rs (Deng and Chen, 2003; Xie et al, 2008), in our hands CTZ reduced only slightly GABA A R activation and exerted no effect on GABA C R activation in response to exogenous GABA puffs (Supplementary Figure 2A–D). We also observed that CTZ potentiated GABA release from A17 amacrine cells when stimulated by exogenous glutamate puffs (to 173 ± 17 % of control response; p = 0.00137; Supplementary Figure 2; Grimes et al 2009).…”
Section: Resultscontrasting
confidence: 59%
“…As shown previously (Singer and Diamond, 2003), blocking AMPAR desensitization with cyclothiazide (CTZ, 50 µM) increased reciprocal GABA release and caused a slower, GABA C R-mediated component to emerge in the reciprocal IPSC (Figure 6A). Although CTZ has been reported to antagonize both GABA A R and GABA C Rs (Deng and Chen, 2003; Xie et al, 2008), in our hands CTZ reduced only slightly GABA A R activation and exerted no effect on GABA C R activation in response to exogenous GABA puffs (Supplementary Figure 2A–D). We also observed that CTZ potentiated GABA release from A17 amacrine cells when stimulated by exogenous glutamate puffs (to 173 ± 17 % of control response; p = 0.00137; Supplementary Figure 2; Grimes et al 2009).…”
Section: Resultscontrasting
confidence: 59%
“…At a concentration of 300 µM, cyclothiazide abolishes GABA responses mediated by ρ2 homomers but has no significant effect on the responses of ρ1 homomers [42]. We therefore examined the effect of cyclothiazide on GABA C R-mediated currents in BCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Amino-acid substitutions in the pore-forming second transmembrane domain, in particular a switch at the 2′ position from proline in ρ1 to serine in ρ2, underlies subunit differences in properties such as deactivation rate, channel conductance and sensitivity to GABA [24], [63], [64]. This amino-acid substitution also underlies the difference in sensitivity to both picrotoxin and cyclothiazide of ρ1 and ρ2 receptors [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclothiazide is a negative modulator of perch q2 GABA C receptors (IC 50 12 lM) without effect on human q1 receptors [79]. In addition to its widespread use as a positive modulator of AMPA receptors, cyclothiazide is a potent negative modulator of GABA A receptors [80].…”
Section: Negative Modulatorsmentioning
confidence: 99%